NaMnO2−x thin nanosheets assembled microspheres as electrode for aqueous asymmetric supercapacitor. (30th March 2020) - Xu, Song; Wan, Tao; Zhou, Kai-bin; Zhu, Guang-ming; He, Zhi-qiang; Huang, Hai-bo; Zhou, Ting; Mao, Wen-qi; Wu, Jie-jun; Gong, Shang-kun; Qiao, Yan-xin
Abstract: This study proposes MnO2 thin nanosheets assembled microspheres with oxygen vacancies and pre-insertion of Na ions (NaMnO2−x ) as highly capable supercapacitor electrodes. The NaMnO2−x electrode can reach a stable potential window of 1.2 V without oxygen evolution reactions in three-electrode configuration. The voltage window of the assembled aqueous ASC device can be expanded to 2.4 V (1 M Na2 SO4 ) by using NaMnO2−x electrode and activated carbon electrode as positive and negative electrodes, respectively. The NaMnO2−x electrode delivers a good specific capacitance of 215 F · g −1 at current density of 1 A · g −1 . It displays high-rate capability and an excellent cycling stability, maintaining 95.5% of its initial specific capacitance at 2 A · g −1 after 2500 cycles. The ASC device shows a high energy density and power density of 28.56 W · h · kg −1 and 1246 W · kg −1, respectively, at a current density of 1 A · g −1 .